1956
DOI: 10.1177/000348945606500203
|View full text |Cite
|
Sign up to set email alerts
|

XXVII Extensive Venous Obstruction of the Labyrinth

Abstract: Vascular lesions of the labyrinth have been under investigation in this laboratory for the past four years. The effect of obstruction of the inferior cochlear vein was reported on in 1952. 1 Only minimal histological change and no functional change as tested electrically was found. Further studies have been made possible by development of a method for direct observation of the vessels in the stria vascularis and spiral ligament through the microscope and recording by means of the motion picture camera.A series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

1958
1958
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(23 citation statements)
references
References 9 publications
0
21
1
1
Order By: Relevance
“…The sequence of cellular damage observed in the present study is different from that produced by the obstruction of the anterior inferior cerebellar artery (Kimura and Perlman, 1958), or the inferior cochlear vein and its collaterals (Kimura and Perlman, 1956). In these cases of whole inner ear ischemia, the stria was reported to detach from the spiral ligament close to the spiral prominence within 1 hour.…”
Section: Discussioncontrasting
confidence: 66%
“…The sequence of cellular damage observed in the present study is different from that produced by the obstruction of the anterior inferior cerebellar artery (Kimura and Perlman, 1958), or the inferior cochlear vein and its collaterals (Kimura and Perlman, 1956). In these cases of whole inner ear ischemia, the stria was reported to detach from the spiral ligament close to the spiral prominence within 1 hour.…”
Section: Discussioncontrasting
confidence: 66%
“…Berg (1951) observed that the otolithic membranes had disappeared in cats treated with streptomycin. Kimura & Perlman (1956) observed the same phenomenon after venous obstruction of the labyrinth. Recently I have observed the loss of otolithic membranes in guinea pigs after middle ear exposure to the disinfectant chlorhexidine (Aursnes, 1980 b).…”
Section: Discussionmentioning
confidence: 56%
“…3,4 In Figure 1, midmodiolar section of guinea pig and cat temporal bones are illustrated. 3,4 In Figure 1, midmodiolar section of guinea pig and cat temporal bones are illustrated.…”
Section: Methodsmentioning
confidence: 99%